Segmentation of consumers and approaches to it: modern accents and aspects of practical application - Churlei, Eduard G.; Kuzmenko, Tatiana V. (Journal of the Belarusian State University. Economics, 2019)
The change in the competitive field is orienting market players to increasing the role of marketing and improving approaches to segmentation. One of the relevant methods of segmentation is the generation theory. The adaptation of segmentation based on this theory for the market made it possible to obtain the psychographic characteristics of the segment of students.
Keywords: сonsumer segmentation; segmentation theory; psychographic segmentation; generation; generational approach; generation theory; consumer research; marketing research; youth; generation Z